The curse of Penryth Hall - Armstrong, Jess (Minotaur Books, 2023)
"An atmospheric gothic mystery that beautifully brings the ancient Cornish countryside to life, Armstrong introduces heroine Ruby Vaughn in her Minotaur Books & Mystery Writers of America First Crime Novel Award-winning debut, The Curse of Penryth Hall. After the Great War, American heiress Ruby Vaughn made a life for herself running a rare bookstore alongside her octogenarian employer and house mate in Exeter. She's always avoided dwelling on the past, even before the war, but it always has a way of finding her. When Ruby is forced to deliver a box of books to a folk healer living deep in the Cornish countryside, she is brought back to the one place she swore she'd never return. A more sensible soul would have delivered the package and left without rehashing old wounds. But no one has ever accused Ruby of being sensible. Thus begins her visit to Penryth Hall. A foreboding fortress, Penryth Hall is home to Ruby's once dearest friend, Tamsyn, and her husband, Sir Edward Chenowyth. It's an unsettling place, and after a more unsettling evening, Ruby is eager to depart. But her plans change when Penryth's bells ring for the first time in thirty years. Edward is dead; he met a gruesome end in the orchard, and with his death brings whispers of a returned curse. It also brings Ruan Kivell, the person whose books brought her to Cornwall, the one the locals call a Pellar, the man they believe can break the curse. Ruby doesn't believe in curses--or Pellars--but this is Cornwall and to these villagers the curse is anything but lore, and they believe it will soon claim its next victim: Tamsyn. To protect her friend, Ruby must work alongside the Pellar to find out what really happened in the orchard that night"--